2022
DOI: 10.1021/acsami.2c10323
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured Bi2S3/MoS2 Nanoarrays for Efficient Electrocatalytic Nitrate Reduction to Ammonia Under Ambient Conditions

Abstract: Developing efficient electrocatalysts to realize the nitrate reduction reaction (eNO 3 − RR) for ammonia synthesis as an alternative to the traditional Haber−Bosch production process is of great significance. Herein, the heterostructured Bi 2 S 3 /MoS 2 nanoarrays were successfully synthesized by Bi 2 S 3 nanowires anchored on MoS 2 nanosheets. Owing to the interfacial coupling effect, both particular surface area and exposure active sites increase. Density functional theory further uncovered that the excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The following proton/electron pair attacks on the dangling oxygen and leads to a NOH pathway with a free energy increase of 0.27 eV, which is also the PDS as described by many reports. 52,55 56 embedded in VASP and displayed the free energy evolution profile in Figure S3, and we confirmed that the solvent effect is negligible in our system.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The following proton/electron pair attacks on the dangling oxygen and leads to a NOH pathway with a free energy increase of 0.27 eV, which is also the PDS as described by many reports. 52,55 56 embedded in VASP and displayed the free energy evolution profile in Figure S3, and we confirmed that the solvent effect is negligible in our system.…”
supporting
confidence: 82%
“…Three possible adsorption configurations of the *NO intermediate are also studied, and the O-end intermediate is the most stable configuration. The following proton/electron pair attacks on the dangling oxygen and leads to a NOH pathway with a free energy increase of 0.27 eV, which is also the PDS as described by many reports. , However, generation of another intermediate (*NHO) is thermodynamically more favorable due to the decrease of Gibbs free energy (−0.37 eV).The further protonation of *NHO could result in two intermediates (*NH 2 O and *NHOH) because of different attacking sites, which endows free energy changes of −0.17 eV and −0.29 eV, respectively. Herein, *NHO + H + + e – → *NH 2 O is excluded and *NHOH formation is preferred, which would be further reduced to form two possible intermediates (*NH 2 OH and *NH).…”
mentioning
confidence: 62%
“…Molybdenum disulfide (MoS 2 ), a promising 2D transition-metal dichalcogenide (TMD) with semiconducting characteristics and tunable band gap, 18 has been used in a variety of optoelectronic applications, including catalysis, energy storage/conversion, and photovoltaic materials, due to its high activity, low toxicity, and good electronic and optical properties. 19 Computational and experimental studies have confirmed that monolayer or few-layer MoS 2 possesses suitable band edge positions to be used as photoanodes for PEC. 20 To date, MoS 2 -based semiconductor heterostructures, such as MoS 2 /WS 2 , 20 CdS/MoS 2 , 21 and Ti 3 C 2 (TiO 2 )@CdS/MoS 2 , 22 have obtained acceptable photocatalytic or PEC performance, due to the effective charge separation by coupling two semiconductors with matching energy levels.…”
Section: Introductionmentioning
confidence: 94%
“…In fact, compared to 0D and 1D materials, 2D heterojunctions are likely to show more efficient charge separation and transfer. Molybdenum disulfide (MoS 2 ), a promising 2D transition-metal dichalcogenide (TMD) with semiconducting characteristics and tunable band gap, has been used in a variety of optoelectronic applications, including catalysis, energy storage/conversion, and photovoltaic materials, due to its high activity, low toxicity, and good electronic and optical properties . Computational and experimental studies have confirmed that monolayer or few-layer MoS 2 possesses suitable band edge positions to be used as photoanodes for PEC .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other metal compounds have also been applied as electrocatalysts for NO 3 − to NH 3 conversion at room temperature. [145][146][147] Zhang et al 148 fabricated Ni 3 N nanoparticles embedded on a carbon skeleton and investigated its electrochemical performance as a catalyst for the NO 3 − RR. This catalyst provided a high NH 3 selectivity of 89.5% and large yield rate of 9.185 mmol h −1 mg −1 at −0.795 V vs. RHE in neutral media.…”
Section: Other Metal Compoundsmentioning
confidence: 99%